Key Directions And Problems Of Professional Training Of Future Teachers Of Foreign Languages - Salima Babaeva, Hilola Alimova, Nafisa Elmuratova, Khojarbibi Ataniyazova, Gavhar Musaeva (International Journal of Advanced Science and Technology, 2020)
The article is devoted to the problems of professional training of future teachers of foreign languages, the definition of its content, approaches, methods and principles. The author sets out his point of view on the causes and consequences of the weakening of the training of these teachers, analyzes language, pedagogical, methodological and sociocultural studies, and also suggests ways to solve the problems highlighted in the article. The article reveals some shortcomings of the modern system of training teachers, placing a special emphasis on the need to strengthen its axiological component, personal-activity nature and the role of culture as the content of humanitarian education.